Static and Dynamic Analysis of Framed-Tube Structures - Chan, Chee-Kin Paul (My University, 1973)
The object of the work investigated in this thesis is to develop an approximate method for static and dynamic analysis of uniform framed-tube structures. The thesis begins with a review of the developments of high-rise constructions and the methods of analysis of high-rise buildings. Then study is carried out to investigate some special structural problems, such as the shear lag effect in the normal frames, which form the flanges of a "perforated tube" structure and the "column shortening effect" of the rectangular frames. Energy approach is used in formulating the problem and approximations are introduced to represent these effects in deriving simple methods of analysis for investigation. The results of the investigation are co-ordinated to develop an approximate method of analysis for tall uniform framed-tube structures subjected to lateral loading. The method is simple enough for computations to be done on a desk calculator or small computer. The theory for static analysis is then extended to determine the dynamic characteristics of such structural system, which are required for seismic analysis based on the response spectrum technique. Experimental work, which includes both static and dynamic testing of a 6 fest plexiglass framed-tube model, is performed for verifying the theory.
An addendum is included to discuss the social and economic aspects of high-rise construction for drawing the attention of those high-rise designers to the reactions of the high-rise users and those concerned.
Keywords: Civil Engineering; Engineering Mechanics; Civil Engineering